Students' learning interest in long jump learning - Rohman Ardiansyah Prakoso; Bambang Ferianto Tjahyo Kuntjoro; Bayu Budi Prakoso (Universitas Sriwijaya, 2022)
The purpose of this study was to determine the level of interest in learning for class IX students in long jump athletic learning at SMP Negeri 1 Wajak. The type of research used is descriptive quantitative with a survey method. This study involved the entire population, namely the entire class IX of SMP Negeri 1 Wajak which consisted of 307 students (male = 144 and female = 163). The survey procedure was carried out in five stages, namely: (1) finding student identities from the data of class IX students through administrative staff, (2) socializing the procedures for filling out questionnaires, (3) distributing questionnaires, (4) tabulation and data analysis; and (5) conclude the results. The data analysis technique used validity (correlation) and reliability (Cronbach's alpha) tests, descriptive statistics, and percentages. The results showed that the instrument used was valid (r= 0.110-0.557>0.105) and reliable (α= 0.857-0.872>0.7). Based on the data distribution, it can be explained that 20 students (6.51%) in the very high category, 205 students (66.78%) in the high category, 79 students (25.73%) in the medium category, 3 students (0.98%) in the low category, 0 students (0%) in the very low category. The average value of psychological aspects is 38.88 in the high category, SD is 5,040, the highest value is 55, and the lowest value is 20. The average psychological value is 29.99 in the high category, SD is 3,864, the highest score is 40, and the lowest score is 14. The average social value of 28.82 in the high category, SD at 3,378, the highest score at 40, and the lowest score at 16. The average non-social score was 14.97 in the high category, SD was 1.909, the highest score was 20, and the lowest score was 7, so it can be concluded that the total average score is 112.6 and in the category of high learning interest.